Recent advances in flexible sweat glucose biosensors. (2nd August 2021) - Zhou, Wenbin; He, Qian; Ye, Haifeng; Ye, Changqing; Wu, Xing; Chu, Junhao
Abstract: Continuous monitoring of the blood glucose levels is necessary for its diagnosis and treatment. In recent years, researchers have discovered a correlation between sweat glucose and blood glucose. The methodology of obtaining the value of blood glucose by detecting glucose in sweat is expected to replace conventional diabetes detection. Flexible sweat glucose biosensor owns the characteristics of stretchability, comfortability, and the capability of non-invasive and is a promising candidate for non-invasive diabetes monitoring. In this review, we summarize the latest developments in research and applications of the flexible sweat glucose biosensors based on enzyme and non-enzymatic detection methodologies. The correction methodologies, challenges and outlooks of the wearable sweat glucose biosensor technology are also be discussed.